Clinical characteristics of patients with pulmonary infarction – A retrospective review. (June 2018) - Chengsupanimit, Tayoot; Sundaram, Baskaran; Lau, Wayne Bond; Keith, Scott W.; Kane, Gregory C.
Abstract: Background: Pulmonary infarction is an infrequent complication of pulmonary embolism. Traditionally, it has been regarded as a sign of worse outcome because ischemia can only occur by the simultaneous failure of all oxygenation sources to the area of infarct, but supporting evidence is limited. Methods: We identified 74 cases of pulmonary infarction over 5 years at a single academic center via review of radiographic reports. Contrast-enhanced chest CT scans were examined to confirm evidence of pulmonary infarction, and patient clinical characteristics and imaging results were studied. Results: Survival to discharge was high (97%). Patients most commonly presented with dyspnea (69%), chest pain (46%), and swelling or pain in the lower extremities (31%), while underlying risk factors included history of malignancy (41%) and surgery within 30 days (24%). Many patients had concurrent cardiovascular (59%) and pulmonary disease (22%). Infarction disproportionately affected the lower lobes. Conclusions: Survival after diagnosis of pulmonary infarction is comparable to uncomplicated pulmonary embolism, suggesting that outcome is not worse. While emboli occurred in multiple lobar sites, pulmonary infarction occurred most commonly in the lower lobes, suggesting unique underlying physiological mechanisms in pulmonary infarction development. Highlights: Pulmonary infarction mortality is comparable to uncomplicated pulmonary embolism. Pulmonary infarction disproportionately occurs in the lower lobes. Hemoptysis was rare in patients who developed pulmonary infarcts.